Climate-Smart Mapping and Adaptation Planning (CS-MAP) Evaluation Report - Pham Thanh Van (2021)
The report elaborates the results and recommendations of an evaluation study on the effectiveness of the development and implementation of the Climate-Smart Mapping and Adaptation Planning (CS-MAP) approach in Vietnam. The results are based on the experiences of the 23 provinces that applied CS-MAP in rice production.